Quality issues of women's apparel from online retailers - Lopez, Mariah Louise B.
Online apparel retailing has been booming since 1999 and the largest chunk of online apparel shoppers are women (Love, 2016). With the eminent growth of the number of apparel stores online it is inevitable for quality issues to arise. One of these is the feedbacks from consumers who experience numerous garment product quality issues with their online purchases. This study aimed to analyze quality concerns in the purchase of online women's apparel consumers. Interviews with selected consumers and selected retailer were conducted to further determine the possible causes of the quality issues, and whether the actions were effective or not. Findings showed that the quality issues can be classsified to five: fit, size, stitching,fabric and accuracy of the photos posted by the retailer compared with actual product received by the consumer.The causes of the garment product quality issues are due to consumer's failure to take their body measurements and compare with the size chart provided by the retailer, as well as the lack of information and misinformation provided about the product.The most effective action by the consumers to resolve the problem is to coordinate with the retailer to return and exchange the item. As for the retailers, they could implement a proper quality control system. For future studies, the researcher recommends getting more respondents and to test the suggestions of the respondents in encountering and preventing quality issues.